2021
DOI: 10.3390/agronomy11061160
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Development and Primary Metabolism in Apple

Abstract: Apples (Malus domestica Borkh.) represent one of the most produced fruits worldwide, along with citrus and bananas. As high quality is an important trait for the consumer, many studies have focused on the research of new techniques to ensure and preserve the optimal organoleptic characteristics of this fruit. However, despite the huge number of studies on recent technological advances dealing with fruit final quality, less research has focused on the physiological aspects of apple development, including a vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In our research, the delay in the harvest date caused the increase in fruit weight. This confirms the theory that fruits increase in diameter and weight until harvest [34][35][36]. During the first harvest date, the IEC was approximately 0.1 ppm, which is often taken as the beginning of the climacteric stage [37].…”
Section: Discussionsupporting
confidence: 83%
“…In our research, the delay in the harvest date caused the increase in fruit weight. This confirms the theory that fruits increase in diameter and weight until harvest [34][35][36]. During the first harvest date, the IEC was approximately 0.1 ppm, which is often taken as the beginning of the climacteric stage [37].…”
Section: Discussionsupporting
confidence: 83%
“…Lastly, significant differences in SSC were observed in 'Royal Gala' trees between all crop load treatments (3, 4, and 5 fruit cm −2 limb cross-sectional area, LCSA), with the highest crop load presenting an average value of 1.1 • Brix lower than the lowest crop load [61]. These results suggest that the effect of crop load on fruit SSC could also depend on other factors, such as apple cultivar, growing conditions, training system, timing of thinning, and additional agronomic practices [62,63].…”
Section: Fruit Non-structural Carbohydrates Soluble Solids Content (S...mentioning
confidence: 93%
“…However, the same authors verified that tomato photosynthesis had a considerable role in seed development, impacting on seed set, composition, and morphology during the early developmental stage. In the same way, a recent review about the primary metabolism of apples, suggested that apple photosynthesis may be mainly used to support seed development and accumulate malate via the malate-CO 2 shuttle [127]. This hypothesis was based on the low rates of CO 2 assimilation in immature apples, as compared to those of the leaves, meaning that the CO 2 fixed in the peel also has little effect on growth and development in this crop [128,129].…”
Section: The Relationship Between Photosynthesis and Metabolism In Fr...mentioning
confidence: 99%
“…Indeed, the CBB cycle can supply precursors for pathways of primary and secondary metabolism (as reviewed for tomato by Cocaliadis et al [113]; and for apple by Tijero et al [127], who highlighted the importance of apple photosynthesis for its primary metabolism). Primary metabolites, such as sugars, organic acids, and amino acids, produced at the early stages of development, determine most of the final fruit quality, as they are the main substrate for many reactions of secondary metabolism.…”
Section: The Relationship Between Photosynthesis and Metabolism In Fr...mentioning
confidence: 99%